Maqāṣid Asy-syarī'ah dan Paradoks Profitabilitas: Tinjauan Sistematis terhadap Strategi Pembiayaan Hijau Bank Syariah Indonesia - Intan Dinda Pertiwi; Arifa Pratami; Ismail (Wahana Islamika Jurnal Studi Keislaman, 2026)
This study aims to analyze the strategy of Bank Syariah Indonesia (BSI) in supporting the green economy through renewable energy financing, specifically examining the dialectic between Maqāṣid Asy-syarī'ah values and financial performance. Employing a Systematic Literature Review (SLR) with the PRISMA protocol, this research synthesizes 10 reputable academic articles published between 2021 and 2025. The findings reveal that BSI plays a strategic role as a technological catalyst and carbon emission mitigator through innovative instruments such as Green Sukuk and Green Murabahah. However, the study identifies a profitability paradox, where green financing correlates negatively with ROA in the short term due to high initial investment costs. BSI mitigates this challenge by leveraging its massive bank size and digitalizing operations under the G-Sharia framework. The study concludes that the integration of Islamic ethics and digital technology enables BSI to balance ecological responsibility with long-term stability. Implicatively, regulatory support in the form of fiscal incentives is essential to mitigate transition risks toward a low-carbon economy within the Islamic banking sector.